UMPSA Excellence Bridging Time with the Spirit of Create, Love and Image - Gunavaathy, Saravanan (UMPSA, 2023)
Stepping onto the threshold of educational excellence, Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) radiates excellence in every corner of its campus. With a strong commitment to fostering success, UMPSA has designed its programmes as launching pads for student excellence in their chosen fields. Going beyond traditional classrooms, UMPSA transforms learning into a journey of real-world problem-solving, accompanied by professional training that guides graduates towards impactful careers.